Viable deletion mutants in the simian virus 40 early region. - Feunteun, J (1978)
For the purpose of isolating hr-t-like mutants of simian virus 40, we have constructed variants that have lost the unique site for the restriction enzyme Taq I at 0.565. Five mutants have been isolated and characterized by restriction enzyme analysis. All of them produce a normal size T antigen. Four produce a t antigen reduced in size as well as in amount; the fifth one does not seem to make any t antigen at all. The ability of these mutants to transform mouse cells in vitro, as tested by anchorage dependence, is clearly altered; however, the defect is only partial. In the same test, the mutants can complement a tsA mutant for transformation and therefore define a second complementation group in the simian virus 40 early region.